Clinical relevance of [i]Corylus[/i] pollen in Poznań, western Poland - Łukasz Grewling; Dorota Jenerowicz; Małgorzata Nowak; Adriana Polańska; Bogdan Jackowiak; Magdalena Czarnecka-Operacz; Matt Smith (Annals of Agricultural and Environmental Medicine, 2014)
Background. In Central Europe, hazel ([i]Corylus[/i] sp.) pollen is considered to be an important aeroallergen in early spring. Objective. This study examines hazel pollen levels in Poznań, western Poland, and the clinical relevance of this aeroallergen in the city. Methods. [i]Corylus[/i] pollen data (1996–2010) were obtained by volumetric spore trap located near the centre of Poznań. Clinical data (2006–2010), i.e. skin prick test (SPT) and allergen-specific IgE measurements (asIgE), were supplied by the Allergy Diseases Diagnostic Centre in Poznań. Results. Mean diurnal hazel pollen concentrations peaked around 14:00–16:00 when mean bi-hourly pollen concentrations were ~60 P m-3. Onset of the hazel pollen season varied up to 87 days annually, and was significantly (r=–0.647; p<0.01) related to mean maximum temperature during late December. SPT data revealed that ~11% of allergy patients had positive skin reactions to [i]Corylus[/i] pollen allergens, and most of these (94.4%) reacted to pollen allergens from other members of the Betulaceae family – alder or birch. Of those sensitized, 53% suffered from atopic dermatitis. Of patients examined for serum asIgE, 26.0% had asIgE measurements in classes 5 and 6. Conclusions. Hazel pollen has a detrimental effect on the allergic population of Poznań, with more than half of those sensitised to hazel pollen allergens showing symptoms of atopic dermatitis. Hazel pollen concentrations reach levels recognized as being able to induce allergy symptoms, especially in the afternoon and early evening when many people are returning home from work. The cross-reactivity with other members of the Fagales order also increases the allergenic potential of hazel pollen.